2020
DOI: 10.1016/j.amsu.2020.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep disorders among medical students and their association with poor academic performance: A cross-sectional study

Abstract: Background Sleep quality is of paramount importance for human health. This multi-site study measures the proportion and types of self-reported sleep disorders in medical students and evaluates their association with academic performance by Grade Point Average (GPA). Materials and methods A cross-sectional survey was conducted on medical students from two medical schools in Jordan during the 2018/2019 academic year. The study utilized the SLEEP-50 questionnaire to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 36 publications
7
37
1
6
Order By: Relevance
“…Also, the participants needed access to a smartphone/computer, which may cause a selection bias, and the response rate was low (16%). However, data completeness was very high, and the participation rate in this study is concordant with previous internet-based surveys ( 65 , 106 , 107 ). Thus, a snowball sampling recruitment method with appropriate incentives is suggested in future studies.…”
Section: Discussionsupporting
confidence: 89%
“…Also, the participants needed access to a smartphone/computer, which may cause a selection bias, and the response rate was low (16%). However, data completeness was very high, and the participation rate in this study is concordant with previous internet-based surveys ( 65 , 106 , 107 ). Thus, a snowball sampling recruitment method with appropriate incentives is suggested in future studies.…”
Section: Discussionsupporting
confidence: 89%
“…The Ogińska's research demonstrated an increased risk of sleep disorders among medical students [3]. According to another study conducted among medical students in Jordan, the incidence of sleep disorders ranged from 0.6% to 23.1% [4]. In the Polish population, almost half of medical students are not satisfied with their sleep, they sleep less than 6 hours a day, with the sleep time variable and irregular [5].…”
Section: The Incidence Of Sleep Disorders Among Doctorsmentioning
confidence: 99%
“…College is a time of intellectual growth and development for adolescents transitioning into adulthood. Often times, students are investing a great deal of time, money, and effort into education, and to successfully get a return on the investment, students feel a need to maximize learning, academic achievement, and personal growth 3,4 . To balance academic, professional, and personal demands, students often make lifestyle changes upon entering college, including sleep.…”
Section: Introductionmentioning
confidence: 99%
“…The susceptibility to poor sleep among college students is partially due to conflicts between college, work, social demands, and individual circadian rhythms 6 . Use of electronics such as cell phones and laptops, and substances such as caffeine, alcohol, and stimulants, as well as individual stress and anxiety also contribute to poor sleep 3,4,7 . Sleepiness and sleep deprivation can have a particularly detrimental effect on college students, with impacts on learning and memory, impaired mood, increased risk of motor vehicle accidents, lower grade point averages, and increased risk of academic failure 3,4,8,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation